Ultra-low thermal expansion coefficient photosensitive polyimide, preparation method and application thereof

CN122984282APending Publication Date: 2026-10-27POME TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610911509.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种超低热膨胀系数光敏聚酰亚胺及其制备方法和应用,其能够解决现有光敏聚酰亚胺热膨胀系数过高、光刻分辨率与低热膨胀系数难以兼得、以及封装热冲击界面开裂的问题

Benefits of technology

[0023]与现有技术相比,本发明的超低热膨胀系数光敏聚酰亚胺及其制备方法和应用,具有以下益处:具有超低热膨胀系数(CTE≤5ppm/°C),避免了传统侧基光敏化对主链刚性棒状结构的破坏,完整保留了联苯型聚酰亚胺的超低CTE特性,从材料源头解决了封装热应力失配问题;高分辨率与超低CTE兼得,通过超声辅助实现了分子级均匀分散,且“链端感光化”主链本身具有良好溶解性,两者协同使得光刻分辨率可满足先进封装对精细线路的苛刻要求;八乙烯基笼型倍半硅氧烷(OV-POSS)的点阵交联网络不仅进一步抑制了分子链的热运动,同时显著提高了材料的玻璃化转变温度(Tg提高10-20°C)和热分解温度(Td提高30-50°C),并增强了薄膜的模量与韧性,有效解决Chiplet封装热冲击开裂难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122984282A_ABST
    Figure CN122984282A_ABST
Patent Text Reader

Abstract

The application discloses a kind of super low thermal expansion coefficient photosensitive polyimide and its preparation method and application, the super low thermal expansion coefficient photosensitive polyimide is negative photosensitive polyimide, it is formed by imidization after the end of biphenyl type polyamide acid chain is capped by photoactive capping agent, and wherein uniformly dispersed with octavinyl cage-type silsesquioxane (OV-POSS). Compared with prior art, the super low thermal expansion coefficient photosensitive polyimide and its preparation method and application of the application have the following benefits: with super low thermal expansion coefficient (CTE≤5ppm / °C), avoid the destruction of traditional side group photosensitization to main chain rigid rod structure;High resolution and super low CTE are obtained;The lattice crosslinking network of octavinyl cage-type silsesquioxane (OV-POSS) not only further inhibits the thermal motion of molecular chain, simultaneously significantly improves the glass transition temperature (Tg increases 10-20°C) and thermal decomposition temperature (Td increases 30-50°C) of material, effectively solve Chiplet packaging thermal shock cracking problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photosensitive materials, specifically relating to an ultra-low thermal expansion coefficient photosensitive polyimide, its preparation method, and its application. Background Technology

[0002] Photosensitive polyimide (PSPI) has become the preferred material for RDL dielectric layers due to its excellent thermal stability, mechanical strength, low dielectric loss, and direct photolithography patterning capabilities. However, existing negative PSPI materials generally suffer from excessively high coefficients of thermal expansion (CTE). The CTE of commercially available negative PSPI is approximately 18–25 ppm / °C, while the CTE of silicon chips in Chiplet / CoWoS packaging is extremely low, only about 3 ppm / °C. This significant mismatch in CTE leads to substantial thermal stress accumulation at the interfaces of multilayer RDL stacks during back-end chip processing and service life, particularly during thermal shocks (such as cycling from -55°C to 125°C). This frequently causes cracking failures at the RDL-chip interface or between different RDL layers, severely limiting the long-term reliability of packaged devices.

[0003] To reduce the thermal expansion coefficient (CTE) of photosensitive polyimides, academia and industry have conducted extensive research. Utilizing the rigid rod-like molecular structure of biphenyl-based polyimides (such as those based on BPDA and PDA or TFMB) is an effective way to achieve ultra-low CTE. However, when converting non-photosensitive ultra-low CTE polyimides into photosensitive PSPIs using traditional methods (i.e., grafting photosensitive groups onto the side groups of the polyamic acid backbone), a fundamental technical drawback is encountered: the introduction of large-volume photosensitive side groups severely disrupts the rigid rod-like stacking and in-plane orientation of the biphenyl-based backbone, causing the CTE to rebound sharply from below 8 ppm / °C in the non-photosensitive state to above 15 ppm / °C, thus losing its advantage of low thermal expansion.

[0004] To compensate for CTE rebound, some studies have attempted to reduce the overall CTE of composite materials by filling with nanofillers (such as cage-like polysilsesquioxane). However, traditional micron-sized or ordinary nano-sized POSS fillers have limited effectiveness in improving CTE due to poor compatibility with the matrix and easy agglomeration. Furthermore, larger particle sizes of fillers can severely scatter exposure light, significantly degrading lithography resolution and making it difficult to meet the patterning requirements of advanced packaging for 5μm or even smaller linewidths / spacings.

[0005] Therefore, in order to address the above-mentioned technical problems, it is necessary to provide a photosensitive polyimide with an ultra-low coefficient of thermal expansion, its preparation method, and its application.

[0006] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention

[0007] The purpose of this invention is to provide a photosensitive polyimide with an ultra-low coefficient of thermal expansion, its preparation method, and its application, which can solve the problems of excessively high coefficient of thermal expansion, difficulty in achieving both photolithographic resolution and low coefficient of thermal expansion, and interface cracking due to thermal shock during packaging of existing photosensitive polyimides.

[0008] To achieve the above objectives, a specific embodiment of the present invention provides the following technical solution:

[0009] An ultra-low thermal expansion coefficient photosensitive polyimide, wherein the ultra-low thermal expansion coefficient photosensitive polyimide is a negative photosensitive polyimide, which is formed by imidizing the chain end of biphenyl polyamic acid after being capped by a photosensitive capping agent, and wherein octavinyl cage-type silsesquioxane (OV-POSS) is uniformly dispersed therein.

[0010] In one or more embodiments of the present invention, the biphenyl-type polyamic acid is prepared by a ternary copolymerization reaction of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA), wherein the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA) is 1:(0.3-0.7):(0.3-0.7).

[0011] In one or more embodiments of the present invention, the photosensitive end-capping agent is selected from one or more of glycidyl methacrylate (GMA), glycidyl acrylate, 2-hydroxyethyl methacrylate (HEMA), and p-aminostyrene, and the molar ratio of the photosensitive end-capping agent to the polyamic acid chain-terminal substance is (1.0 to 2.0):1.

[0012] In one or more embodiments of the present invention, the octavinyl cage-type silsesquioxane (OV-POSS) has a particle size of <1.5 nm and its mass fraction in the photosensitive polyimide is 1% to 10%.

[0013] This invention also discloses a method for preparing ultra-low thermal expansion coefficient photosensitive polyimide, comprising the following steps:

[0014] (1) Under inert gas protection, the diamine monomers 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB) and 4,4'-diaminodiphenyl ether (ODA) are dissolved in an organic solvent, and the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) is added to carry out a polymerization reaction to obtain a biphenyl-type ternary copolymer polyamic acid solution;

[0015] (2) Add a photosensitive end-capping agent to the polyamic acid solution obtained in step (1) to carry out the chain end-capping reaction, and graft the photosensitive group to both ends of the polyamic acid molecular chain to obtain a chain end photosensitive polyamic acid solution;

[0016] (3) Disperse octavinyl cage-type silsesquioxane (OV-POSS) in an organic solvent to form a pre-dispersion. Add the pre-dispersion to the chain-end photosensitive polyamic acid solution obtained in step (2) and stir to disperse evenly to obtain a chain-end photosensitive polyamic acid composition containing octavinyl cage-type silsesquioxane (OV-POSS).

[0017] (4) Spin-coat the composition obtained in step (3) onto the substrate surface, pre-bake, expose and develop to form a photolithographic pattern, and then perform segmented thermal curing to obtain ultra-low thermal expansion coefficient photosensitive polyimide.

[0018] In one or more embodiments of the present invention, the polymerization reaction temperature in step (1) is 0 to 30°C and the reaction time is 6 to 24 hours; the chain end capping reaction temperature in step (2) is 40 to 80°C and the reaction time is 2 to 8 hours.

[0019] In one or more embodiments of the present invention, the ultrasonic dispersion time in step (3) is 5 to 30 minutes and the ultrasonic power is 100 to 500 W; the amount of octavinyl cage silsesquioxane (OV-POSS) added is 1% to 10% based on the total mass of the final photosensitive polyimide.

[0020] In one or more embodiments of the present invention, the segmented thermosetting process in step (4) is as follows: first segment, heat preservation at 150°C for 30 to 60 minutes; second segment, heat preservation at 230°C for 30 to 60 minutes; third segment, heat preservation at 300 to 350°C for 30 to 120 minutes.

[0021] The present invention also discloses the application of ultra-low thermal expansion coefficient photosensitive polyimide, which is used as a dielectric layer material for Chiplet / CoWoS heterogeneous integrated packaging multilayer RDL, as an interlayer dielectric layer, insulating layer or passivation layer between silicon core and wafer substrate.

[0022] In one or more embodiments of the present invention, the ultra-low thermal expansion coefficient of the photosensitive polyimide is ≤5ppm / °C, and after 1000 thermal shock cycles at -55°C to 125°C, no cracking or delamination is observed at the interfaces between the RDL layer and the silicon core particles, or between the RDL layers.

[0023] Compared with existing technologies, the ultra-low coefficient of thermal expansion photosensitive polyimide, its preparation method, and its application of the present invention have the following advantages: It possesses an ultra-low coefficient of thermal expansion (CTE≤5ppm / °C), avoiding the damage to the rigid rod-like structure of the main chain caused by traditional side-group photosensitization, and fully preserving the ultra-low CTE characteristics of biphenyl-type polyimide, thus solving the problem of thermal stress mismatch in packaging from the material source; it achieves both high resolution and ultra-low CTE, realizing molecular-level uniform dispersion through ultrasonic assistance, and the "chain-end photosensitive" main chain itself has good solubility. The synergy of these two factors allows the photolithography resolution to meet the stringent requirements of advanced packaging for fine lines; the lattice crosslinking network of octavinyl cage-type silsesquioxane (OV-POSS) not only further suppresses the thermal motion of molecular chains but also significantly increases the glass transition temperature (Tg increases by 10-20°C) and thermal decomposition temperature (Td increases by 30-50°C), and enhances the modulus and toughness of the film, effectively solving the problem of thermal shock cracking in chiplet packaging. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a molecular structure diagram of a photosensitive polyimide with an ultra-low coefficient of thermal expansion in one embodiment of the present invention. Detailed Implementation

[0026] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions in the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.

[0027] like Figure 1 As shown, an ultra-low coefficient of thermal expansion photosensitive polyimide in one embodiment of the present invention has an ultra-low coefficient of thermal expansion (CTE≤5ppm / °C), which avoids the destruction of the rigid rod-like structure of the main chain by traditional side group photosensitization and fully preserves the ultra-low CTE characteristics of biphenyl-type polyimide.

[0028] I. Raw Material Sources and Specifications

[0029] The main raw materials used in the examples and comparative examples are as follows:

[0030]

[0031] II. Performance Testing Methods

[0032] (1) Coefficient of thermal expansion (CTE) test: Using a thermomechanical analyzer (TMA, model TA Q400), the temperature was increased from room temperature to 350°C at a rate of 5°C / min under a nitrogen atmosphere. The in-plane thermal expansion coefficient of the film was taken in the range of 50 to 300°C. Each sample was tested three times and the average value was taken.

[0033] (2) Photolithography resolution test: Using an i-line stepper (365nm), the photoresist composition was spin-coated onto a 4-inch silicon wafer, pre-baked and then exposed and developed. The photolithography pattern was observed using a scanning electron microscope (SEM, Hitachi S-4800) to evaluate the limit resolution (line width / spacing L / S=1:1).

[0034] (3) FT-IR spectroscopy test: A Nicolet iS50 FT-IR spectrometer was used in attenuated total reflectance (ATR) mode with a scanning range of 4000-500 cm⁻¹ to confirm the end-capping reaction and the degree of imidization.

[0035] (4) Glass transition temperature (Tg) test: Tg was determined using a differential scanning calorimeter (DSC, TA Q2000) under nitrogen atmosphere at a heating rate of 10°C / min and a two-stage heating curve.

[0036] (5) Thermogravimetric temperature (Td5%) test: Thermogravimetric analyzer (TGA, TA Q500) was used in a nitrogen atmosphere with a heating rate of 10°C / min to record the temperature when the weight loss was 5%.

[0037] (6) Thermal shock reliability test: According to JESD22-A104 standard, the packaged device is placed in a thermal shock chamber under the conditions of -55°C (for 15 minutes) to 125°C (for 15 minutes), with a gas-to-gas transition time of ≤1 minute, for 1000 cycles. After every 200 cycles, the interface between the RDL layer and the silicon core and the interfaces between each RDL layer are observed with an optical microscope to see if cracks or delamination occur.

[0038] III. Performance of Examples and Comparative Examples

[0039]

[0040] Example 1

[0041] (1) Synthesis of biphenyl-type terpolymer polyamic acid

[0042] In a dry 500 mL three-necked flask, add 180 mL of N-methylpyrrolidone (NMP), 12.67 g (0.0375 mol) of 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB) and 7.51 g (0.0375 mol) of 4,4'-diaminodiphenyl ether (ODA), purge with nitrogen, and stir mechanically until completely dissolved. Place the reaction flask in an ice-water bath to lower the system temperature to 0–5°C. Add 22.06 g (0.075 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) in three batches, stirring for 30 minutes after each addition. After the additions are complete, remove the ice bath and continue stirring at 25°C for 12 hours to obtain a light yellow, transparent, viscous polyamic acid solution with a solid content of approximately 15%. The molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA) is 1:0.5:0.5.

[0043] (2) Photosensitive end capping of chain end

[0044] 1.70 g (approximately 0.012 mol) of glycidyl methacrylate (GMA) was added to the above polyamic acid solution. Calculations showed that the amount of terminal polyamic acid chain material was approximately 0.008 mol (theoretical value based on a slight excess of diamine), and the ratio of GMA to terminal polyamic acid chain material was approximately 1.5:1. The mixture was heated to 60°C and stirred for 4 hours under nitrogen protection to induce esterification of the carboxyl groups at the ends of the polyamic acid chains with GMA, grafting photosensitive methacrylate groups onto both ends of the molecular chain. After the reaction, samples were taken for FT-IR analysis. The characteristic absorption peak of the ester carbonyl group appeared at 1720 cm⁻¹, indicating successful end-capping.

[0045] (3) Introduction and dispersion of octavinyl cage-type silsesquioxane (OV-POSS)

[0046] Weigh 1.07 g of octavinyl cage-like silsesquioxane (OV-POSS, particle size approximately 1.2 nm) (approximately 3% by mass based on a final total mass of approximately 35 g of photosensitive polyimide), dissolve it in 20 mL of N-methylpyrrolidone (NMP), and ultrasonically disperse it for 15 minutes at 300 W to obtain a uniform and transparent pre-dispersion of octavinyl cage-like silsesquioxane (OV-POSS). Slowly add this pre-dispersion dropwise to the previous chain-end photosensitive polyamic acid solution while stirring. After the addition is complete, continue stirring for 60 minutes to ensure that the octavinyl cage-like silsesquioxane (OV-POSS) is uniformly dispersed in the polyamic acid matrix.

[0047] (4) Formulation of photoresist composition

[0048] Add photoinitiator Irgacure907 (2% of the solid content of the solution, i.e., about 0.7g) and leveling agent BYK-307 (0.1% of the solid content, i.e. about 0.035g) to the solution obtained in the previous step. After stirring evenly, filter through a 0.45μm PTFE filter membrane and degas under reduced pressure to obtain a negative photosensitive polyimide photoresist composition.

[0049] (5) Spin coating, photolithography and curing

[0050] The above photoresist composition was dropped onto a 4-inch clean silicon wafer and spin-coated at 1500 rpm for 60 seconds to achieve a wet film thickness of approximately 15 μm. The wafer was then preheated on a hot plate at 120°C for 2 minutes to remove most of the solvent. Exposure was performed using i-line ultraviolet light (365 nm) through the mask at an exposure dose of 250 mJ / cm². After exposure, the wafer was immersed in propylene glycol methyl ether acetate (PGMEA) developer for 60 seconds to dissolve unexposed areas. The wafer was then rinsed with isopropanol and dried with nitrogen.

[0051] The patterned silicon wafer is placed in a tube furnace and thermo-cured in stages under nitrogen protection according to the following procedure: the temperature is increased to 150°C at 5°C / min and held for 30 minutes; then increased to 230°C at 3°C / min and held for 30 minutes; finally, the temperature is increased to 330°C at 3°C / min and held for 60 minutes. After natural cooling to room temperature, a photosensitive polyimide dielectric film with an ultra-low coefficient of thermal expansion is obtained.

[0052] (6) Performance testing

[0053] CTE: 3.2ppm / °C (50~300°C)

[0054] Photolithography resolution: 5μm linewidth, complete and clear pattern, no resist floating or collapse.

[0055] Tg: 372°C (DSC)

[0056] Td5%: 535°C

[0057] Film tensile strength: 158 MPa

[0058] Elongation at break: 28%

[0059] Example 2

[0060] This embodiment is basically the same as Example 1, except that the molar ratio of 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB) to 4,4'-diaminodiphenyl ether (ODA) is adjusted to increase the proportion of rigid segments.

[0061] (1) Synthesis of polyamic acid

[0062] Feed quantities: 15.33 g (0.045 mol) of 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), 6.01 g (0.030 mol) of 4,4'-diaminodiphenyl ether (ODA), 22.06 g (0.075 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 180 mL of N-methylpyrrolidone (NMP) solvent. The molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA):4,4'-(hexafluoroisopropyl)diphenylamine (TFMB):4,4'-diaminodiphenyl ether (ODA) was 1:0.6:0.4. The remaining procedures were the same as in Example 1.

[0063] (2) to (6) are the same as in Example 1.

[0064] Performance test results:

[0065] CTE: 2.8ppm / °C

[0066] Photolithography resolution: 5 μmL / S (clear)

[0067] Tg: 385°C

[0068] Td5%: 542°C

[0069] Tensile strength: 165MPa

[0070] Elongation at break: 24%

[0071] Example 3

[0072] This embodiment is basically the same as Example 1, except that the mass fraction of octavinyl cage-type silsesquioxane (OV-POSS) is adjusted to 5%.

[0073] (3) Introduction of octavinyl cage-type silsesquioxane (OV-POSS)

[0074] Amount of octavinyl cage-type silsesquioxane (OV-POSS): 1.80 g (approximately 5% by mass based on a final total mass of about 36 g of photosensitive polyimide). The rest is the same as in Example 1.

[0075] Performance test results:

[0076] CTE: 2.5ppm / °C

[0077] Photolithography resolution: 5 μmL / S (Due to the increase in POSS content, the light transmittance is slightly reduced, and the resolution is slightly lower, but it still meets the requirements).

[0078] Tg: 392°C

[0079] Td5%: 555°C

[0080] Tensile strength: 170 MPa

[0081] Elongation at break: 22%

[0082] Example 4

[0083] This embodiment is basically the same as Example 1, except that the photosensitive capping agent is p-aminostyrene instead of GMA, and the capping reaction conditions are adjusted.

[0084] (2) Photosensitive end capping of chain end

[0085] The polyamic acid solution was cooled to 0–5°C, and 1.43 g (0.012 mol, molar ratio of p-aminostyrene to the chain-terminal substance was added. While stirring, 2.48 g (0.012 mol) of N,N'-dicyclohexylcarbodiimide (DCC) was slowly added dropwise as a condensing agent. The reaction was maintained at 0–5°C for 6 hours to allow the amino group to react with the carboxyl group at the polyamic acid chain terminal to form an amide. After the reaction was complete, the dicyclohexylurea byproduct was removed by filtration. The remaining steps were the same as in Example 1.

[0086] Performance test results:

[0087] CTE: 3.5ppm / °C

[0088] Photolithographic resolution: 4 μmL / s (higher photosensitivity with aminostyrene end capping)

[0089] Tg: 368°C

[0090] Td5%: 528°C

[0091] Example 5

[0092] This embodiment is basically the same as Embodiment 1, except that the ternary copolymer ratio is changed and the proportion of flexible segments is increased to improve processability.

[0093] (1) Synthesis of polyamic acid

[0094] Feed amounts: 8.02 g (0.0225 mol) of 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), 10.51 g (0.0525 mol) of 4,4'-diaminodiphenyl ether (ODA), and 22.06 g (0.075 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA). The molar ratio of BPDA to TFMB to ODA is 1:0.3:0.7. The rest is the same as in Example 1.

[0095] Performance test results:

[0096] CTE: 4.3 ppm / °C (The increase in CTE is due to the increase in flexible segments)

[0097] Photolithographic resolution: 5 μmL / S

[0098] Tg: 335°C

[0099] The film exhibits improved flexibility and an elongation at break of 35%.

[0100] Comparative Example 1 (Traditional side-group photosensitization, without octavinyl cage silsesquioxane (OV-POSS))

[0101] Polyamic acid was synthesized using the same feed ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA) as in Example 1. Instead of chain end capping, after polyamic acid synthesis, 4.26 g of GMA (0.03 mol, approximately 20% of the amount of the main chain repeating unit) and 0.5 g of N,N-dimethylaminopyridine (DMAP) catalyst were added. The reaction was carried out at 60°C for 8 hours, allowing GMA to randomly esterify with the carboxyl groups on the polyamic acid backbone, introducing photosensitive side groups. Octadecylvinyl cage-like silsesquioxane (OV-POSS) was not added. Subsequent photoresist preparation, photolithography, and curing were the same as in Example 1.

[0102] Performance test results:

[0103] CTE: 16.8 ppm / °C (significantly higher than the example).

[0104] Photolithography resolution: 2 μmL / S (good resolution, but CTE is too high)

[0105] Tg: 305°C

[0106] Td5%: 490°C

[0107] Conclusion: Although traditional side-chain photosensitization methods can achieve good lithographic resolution, they severely damage the rigidity of the main chain, leading to a significant rebound in CTE.

[0108] Comparative Example 2 (only chain-end photosensitive, without octavinyl cage silsesquioxane (OV-POSS))

[0109] The chain-end photosensitive polyamic acid (GMA-terminated) was prepared according to steps (1) and (2) of Example 1, but without adding octavinyl cage silsesquioxane (OV-POSS) (i.e., step (3) was omitted). Subsequent photoresist preparation, photolithography, and curing were the same as in Example 1.

[0110] Performance test results:

[0111] CTE: 4.5ppm / °C

[0112] Photolithographic resolution: 5 μmL / S

[0113] Tg: 365°C

[0114] Td5%: 530°C

[0115] Conclusion: Low CTE (4.5 ppm / °C) can be achieved by end-chain photosensitive only, but the CTE is further reduced to 2.8-3.2 ppm / °C after the addition of octavinyl cage silsesquioxane (OV-POSS) (as in Examples 1 and 2), and Tg is also increased by 10-20°C, indicating that the lattice crosslinking of octavinyl cage silsesquioxane (OV-POSS) has a significant synergistic effect.

[0116] Comparative Example 3 (Traditional large-particle-size POSS filling, side group photosensitization)

[0117] Side-group photosensitive polyamic acid was prepared according to the method of Comparative Example 1, but 5% by mass of ordinary POSS (particle size approximately 15–30 nm, non-octavinyl cage-type silsesquioxane (OV-POSS)) was added to the composition. The POSS was added directly to the mixture without ultrasonic pre-dispersion. Subsequent steps were the same as in Example 1.

[0118] Performance test results:

[0119] CTE: 12.5 ppm / °C (lower than Comparative Example 1, but still relatively high)

[0120] Photolithography resolution: approximately 8 μmL / s (severe POSS aggregation and light scattering lead to resolution degradation).

[0121] After development, the film surface is rough, with large linewidth and edge roughness.

[0122] Conclusion: Traditional large-particle-size POSS filling has limited improvement on CTE and severely degrades lithography resolution, failing to meet advanced packaging requirements.

[0123] Comparative Example 4 (commercially available negative photosensitive polyimide)

[0124] A commercially available negative photosensitive polyimide from a well-known brand (used for the RDL dielectric layer, model A) was selected and spin-coated, exposed, developed, and cured according to the recommended process.

[0125] Performance test results:

[0126] CTE: 21ppm / °C (nominal value as stated in the product specification sheet)

[0127] Photolithographic resolution: 5 μmL / S

[0128] Tg: 320°C

[0129] This invention also discloses the application of photosensitive polyimide with ultra-low coefficient of thermal expansion:

[0130] Application Example 1: Fabrication of Multilayer RDL Dielectric Layers for Chiplet / CoWoS Packaging

[0131] The ultra-low thermal expansion coefficient photosensitive polyimide composition prepared in Example 2 was applied to a Chiplet / CoWoS packaging structure. On a 12-inch wafer, a first layer of RDL copper lines was first formed, then the photosensitive polyimide composition of this invention was spin-coated. After pre-baking, exposure, and development, through-hole patterns were formed, followed by segmented curing to form a dielectric layer (10 μm thick). The above steps were repeated to fabricate a 3-layer RDL / dielectric layer stack structure. Finally, silicon cores (10 mm × 10 mm, CTE approximately 3 ppm / °C) were flip-chip bonded to the top layer of the RDL using microbumps.

[0132] Application Example 2: Thermal Shock Reliability Testing

[0133] According to JESD22-A104 standard, the above-mentioned packaged device was subjected to thermal shock cycling test (-55°C to 125°C, 1000 cycles). After every 200 cycles, the interface between the RDL layer and the silicon core, and the interface state between the dielectric layers of each RDL layer were examined using an optical microscope. The results showed:

[0134] The device using the photosensitive polyimide of Example 2: after 1000 cycles, all interfaces remained intact, without cracking or delamination.

[0135] Using a comparative device (conventional side-based photosensitive PSPI) as an example: after about 300 cycles, obvious microcracks appeared at the interface between the RDL and the silicon core particles; after 500 cycles, the cracks propagated and caused some RDL circuits to be open.

[0136] Using Comparative Example 4 (commercially available PSPI): interface delamination occurred after approximately 200 cycles.

[0137] Conclusion: The ultra-low coefficient of thermal expansion photosensitive polyimide (CTE≤5ppm / °C) of the present invention is highly matched with the CTE of silicon core particles, and can withstand 1000 severe thermal shocks without interface cracking, which is significantly better than the prior art.

[0138] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0139] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A photosensitive polyimide with an ultra-low coefficient of thermal expansion, characterized in that, The ultra-low thermal expansion coefficient photosensitive polyimide is a negative photosensitive polyimide, which is formed by imidizing the chain end of biphenyl polyamic acid after being capped by a photosensitive capping agent, and contains uniformly dispersed octavinyl cage-type silsesquioxane (OV-POSS).

2. The ultra-low thermal expansion coefficient photosensitive polyimide according to claim 1, characterized in that, The biphenyl-type polyamic acid is prepared by a ternary copolymerization reaction of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA). The molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB), and 4,4'-diaminodiphenyl ether (ODA) is 1:(0.3-0.7):(0.3-0.7).

3. The ultra-low thermal expansion coefficient photosensitive polyimide according to claim 1, characterized in that, The photosensitive end-capping agent is selected from one or more of glycidyl methacrylate (GMA), glycidyl acrylate, 2-hydroxyethyl methacrylate (HEMA), and p-aminostyrene, and the molar ratio of the photosensitive end-capping agent to the polyamic acid chain-terminal substance is (1.0~2.0):

1.

4. The ultra-low thermal expansion coefficient photosensitive polyimide according to claim 1, characterized in that, The octavinyl cage-type silsesquioxane (OV-POSS) has a particle size of <1.5 nm and its mass fraction in the photosensitive polyimide is 1% to 10%.

5. The method for preparing the ultra-low thermal expansion coefficient photosensitive polyimide according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Under the protection of an inert gas, the diamine monomers 4,4'-(hexafluoroisopropyl)diphenylamine (TFMB) and 4,4'-diaminodiphenyl ether (ODA) are dissolved in an organic solvent, and the dianhydride monomer 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) is added to carry out a polymerization reaction to obtain a biphenyl-type ternary copolymer polyamic acid solution; (2) Add a photosensitive end-capping agent to the polyamic acid solution obtained in step (1) to carry out the chain end-capping reaction, and graft the photosensitive group to both ends of the polyamic acid molecular chain to obtain a chain end photosensitive polyamic acid solution; (3) The octavinyl cage-type silsesquioxane (OV-POSS) is ultrasonically dispersed in an organic solvent to form a pre-dispersion. The pre-dispersion is added to the chain-end photosensitive polyamic acid solution obtained in step (2), and stirred and dispersed evenly to obtain a chain-end photosensitive polyamic acid composition containing octavinyl cage-type silsesquioxane (OV-POSS). (4) Spin-coat the composition obtained in step (3) onto the substrate surface, pre-bake, expose and develop to form a photolithographic pattern, and then perform segmented thermal curing to obtain ultra-low thermal expansion coefficient photosensitive polyimide.

6. The method for preparing ultra-low thermal expansion coefficient photosensitive polyimide according to claim 5, characterized in that, In step (1), the polymerization reaction temperature is 0–30°C and the reaction time is 6–24 hours; in step (2), the chain end capping reaction temperature is 40–80°C and the reaction time is 2–8 hours.

7. The method for preparing ultra-low thermal expansion coefficient photosensitive polyimide according to claim 5, characterized in that, In step (3), the ultrasonic dispersion time is 5 to 30 minutes and the ultrasonic power is 100 to 500W; the amount of octavinyl cage silsesquioxane (OV-POSS) added is 1% to 10% based on the total mass of the final photosensitive polyimide.

8. The method for preparing ultra-low thermal expansion coefficient photosensitive polyimide according to claim 5, characterized in that, The segmented thermosetting process in step (4) is as follows: first segment, keep warm at 150°C for 30 to 60 minutes; second segment, keep warm at 230°C for 30 to 60 minutes; third segment, keep warm at 300 to 350°C for 30 to 120 minutes.

9. The application of the ultra-low coefficient of thermal expansion photosensitive polyimide according to any one of claims 1 to 4 or the ultra-low coefficient of thermal expansion photosensitive polyimide prepared by the preparation method according to any one of claims 5 to 8, characterized in that, The photosensitive polyimide is used as the dielectric layer material of the Chiplet / CoWoS heterogeneous integrated package multilayer RDL, serving as an interlayer dielectric layer, insulating layer, or passivation layer between the silicon core and the wafer substrate.

10. The application of the ultra-low thermal expansion coefficient photosensitive polyimide according to claim 9, characterized in that, The ultra-low thermal expansion coefficient of the photosensitive polyimide is ≤5ppm / °C. After 1000 thermal shock cycles at -55°C to 125°C, no cracking or delamination was observed at the interfaces between the RDL layer and the silicon core particles, or between the RDL layers.